Antibody responses following induction of antigen-specific tolerance with antigen-coupled cells - Peschl, Patrick; Reindl, Markus; Schanda, Kathrin; Sospedra, Mireia; Martin, Roland; Lutterotti, Andreas (Multiple sclerosis, 2015)
We have recently demonstrated the safety and tolerability of a novel therapeutic regimen employing autologous blood cells chemically coupled with seven myelin peptides to induce antigen-specific tolerance in MS (ETIMS study). The aim of the current study was an extended safety analysis to assess the effect of the ETIMS approach on antibodies to common autoantigens, the myelin peptides used and common recall antigens. None of the patients showed induction of autoantibody responses. One patient had a measurable myelin peptide-specific response at baseline, which was reduced after treatment. Total immunoglobulins and recall antibody responses showed no significant change.